Déficit de atención con hiperactividad en niños de la Institución Educativa Inicial N° 343 Corazón de Jesús, Islandia 2022 - Mozombite Pinedo, Mirsia Marlen (2023)
The purpose of this study is to provide an answer to the question: What is the attention deficit level with hyperactivity in children of the initial educational institution N° 343 Corazón de Jesús Iceland 2022? In addition to the main objective of the research: Describe the deficit level of attention with hyperactivity in children of the initial educational institution N° 343 Corazón de Jesús Iceland 2022. For this purpose, the type of descriptive research was adopted and to carry it out, a cross-sectional, field, and univariate design was used. The 125 children were the study population and sample respectively, under the perception of the teacher and parent who observed them through observation guides previously validated by experts. The findings show that there is a perception that the level of hyperactivity with attention deficit of the 125 (100.0%) of the children from 3 to 5 years of the I.E.I Nº 343 "Heart of Jesus" of Iceland, is that in Most of the children 60.8% (n=76) are without suspicion of hyperactivity with attention deficit while 39.2% (n= 49) do have a level of suspicion of hyperactivity with attention deficit.